2015 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2015
DOI: 10.1109/iros.2015.7353743
|View full text |Cite
|
Sign up to set email alerts
|

Robust trajectory selection for rearrangement planning as a multi-armed bandit problem

Abstract: Abstract-We present an algorithm for generating openloop trajectories that solve the problem of rearrangement planning under uncertainty. We frame this as a selection problem where the goal is to choose the most robust trajectory from a finite set of candidates. We generate each candidate using a kinodynamic state space planner and evaluate it using noisy rollouts.Our key insight is we can formalize the selection problem as the "best arm" variant of the multi-armed bandit problem. We use the successive rejects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…We use a similar kinodynamic RRT planner to generate demonstrations in different task instances. There are planners which also take uncertainty into account before the generation of the motion trajectory [13,34,25,43], but these planners typically rely on uncertainty reducing actions, which generate a conservative sequence of actions, limiting the robot from using the complete dynamics of the domain. Alternatively, to avoid the uncertainty associated with multiple objects interacting in a cluttered environment, planning approaches have been developed to avoid contact altogether with environment obstacles.…”
Section: Related Workmentioning
confidence: 99%
“…We use a similar kinodynamic RRT planner to generate demonstrations in different task instances. There are planners which also take uncertainty into account before the generation of the motion trajectory [13,34,25,43], but these planners typically rely on uncertainty reducing actions, which generate a conservative sequence of actions, limiting the robot from using the complete dynamics of the domain. Alternatively, to avoid the uncertainty associated with multiple objects interacting in a cluttered environment, planning approaches have been developed to avoid contact altogether with environment obstacles.…”
Section: Related Workmentioning
confidence: 99%
“…Non-prehensile actions have also been explored as they can simultaneously move multiple objects [40]- [42], quickly declutter a scene and help minimize uncertainty [43] under a conformant probabilistic planning formulation [44], [45]. Though predicting the effect of pushing actions has been studied [46], [47], they are not as predictable as prehensile ones.…”
Section: Related Workmentioning
confidence: 99%
“…7 Koval et al demonstrated a similar passive approach. 8 The approach presented in this paper is different in that it does not explicitly model the uncertainties of the assembly task, but relies on probabilistic effects to eventually handle errors rather than trying to avoid them.…”
Section: Introductionmentioning
confidence: 99%